2013
DOI: 10.1017/jns.2012.20
|View full text |Cite
|
Sign up to set email alerts
|

Feed allowance and maternal backfat levels during gestation influence maternal cortisol levels, milk fat composition and offspring growth

Abstract: The fetal and early postnatal environment can have a long-term influence on offspring growth. Using a pig model, we investigated the effects of maternal body condition (thin or fat) and maternal gestation feeding level (restricted, control or high) on maternal stress, milk composition, litter size, piglet birth weight and pre-weaning growth. A total of sixty-eight thin (backfat depth about 8 mm) and seventy-two fat (backfat depth about 12 mm) gilts were selected at about 22 weeks. This backfat difference was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 63 publications
(74 reference statements)
7
45
1
Order By: Relevance
“…Positive correlations between sow body weight and piglet birth weight have recently been observed by Lewis and Bunter (2011). Interestingly, in the current study Fat gilts had a 25% increase in milk fat at day 21 of lactation than Thin gilts (Amdi et al, 2013), which may have contributed to the increased piglet weight gain. In agreement with our results, Long et al (2010), found that offspring born from obese ewes, consumed 10% more feed than offspring born from control ewes when the offspring where ad libitum fed over a 12-week period from 19.5 ± 0.5 months of age.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Positive correlations between sow body weight and piglet birth weight have recently been observed by Lewis and Bunter (2011). Interestingly, in the current study Fat gilts had a 25% increase in milk fat at day 21 of lactation than Thin gilts (Amdi et al, 2013), which may have contributed to the increased piglet weight gain. In agreement with our results, Long et al (2010), found that offspring born from obese ewes, consumed 10% more feed than offspring born from control ewes when the offspring where ad libitum fed over a 12-week period from 19.5 ± 0.5 months of age.…”
Section: Discussionsupporting
confidence: 57%
“…The effect of the gilt feed level during pregnancy on offspring growth and physiological parameters Gilts fed Restricted feed levels during gestation gave birth to lighter piglets (Amdi et al, 2013), most likely due to inadequate nutrition in utero, as previously seen in sheep (Redmer et al, 2004). Restricted gilts had lower concentrations of IGF-1 than Control and High feed level gilts.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations